Democracy in Action: Experiencing Transformative Education - Jimena Vazquez Garcia; Jason Glynos; Claudia Mohor Valentino; Konstantinos Roussos; Anne Steinhoff; Rebecca Warren; Samantha Woodward; Julius Schneider; Christopher Cunningham (Education Sciences)
Our time is one of permacrisis, affecting the economy, the environment, and everything in between. In this context, UK higher education faces an existential crisis, where the university sector has been transformed into a marketplace, turning students into consumers and limiting the critical potential of education. In moving beyond these limits, this article explores Democracy in Action (DinA), a final-year undergraduate module offered in a UK university that creates spaces for critical and transformative education through democratic theory and practice. Grounded in traditions of transformative learning, community-based pedagogies, academic activism, and prefiguration, DinA positions students as democratic agents working in solidarity with staff and the wider community. Drawing on in-depth interviews with students, we analyse the interplay between theory and practice to understand how learning can be understood as a form of democratic participation. The article makes an original contribution to the fields of democratic education and critical university studies by offering a novel framework for integrating academic activism, community-based learning, and prefiguration in higher education. We show how students’ experiences of building community, campaign planning, and prefiguring change generate not only deep transformative learning but also new forms of civic agency and collective action. We argue that, through community organising, students embark on a process of learning that involves three key transformative moments: effecting a perspectival shift from the individual to the common, foregrounding the activist dimensions of democratic politics, and envisioning the world we want through prefiguration. This pedagogical model demonstrates that higher education can become a space of lived democratic possibility, where hope, critique, and collective transformation are not only imagined but enacted.